2015
DOI: 10.1186/s12909-015-0292-7
|View full text |Cite
|
Sign up to set email alerts
|

Digital rectal examination skills: first training experiences, the motives and attitudes of standardized patients

Abstract: BackgroundPhysical clinical examination is a core clinical competence of medical doctors. In this regard, digital rectal examination (DRE) plays a central role in the detection of abnormalities of the anus and rectum. However, studies in undergraduate medical students as well as newly graduated doctors show that they are insufficiently prepared for performing DRE. Training units with Standardized Patients (SP) represent one method to deliver DRE skills. As yet, however, it is little known about SPs’ attitudes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…Plenty of adipose tissue in pelvic cavity could interfere with the result of DRE. Marshall and Nikendei also found that the prostate could be examined by DRE completely in 91.7% of patients with a BMI below 25 kg/m2, and in 14.3% of those with a BMI above 40 kg/m2, which was consistent with our results31, 32. In addition, a total of 3 false-positive DRE results were found, in which 2 were confirmed as uterine fibroids and 1 was confirmed as prostate nodular hyperplasia intraoperatively.…”
Section: Discussionsupporting
confidence: 90%
“…Plenty of adipose tissue in pelvic cavity could interfere with the result of DRE. Marshall and Nikendei also found that the prostate could be examined by DRE completely in 91.7% of patients with a BMI below 25 kg/m2, and in 14.3% of those with a BMI above 40 kg/m2, which was consistent with our results31, 32. In addition, a total of 3 false-positive DRE results were found, in which 2 were confirmed as uterine fibroids and 1 was confirmed as prostate nodular hyperplasia intraoperatively.…”
Section: Discussionsupporting
confidence: 90%
“…The former intends to check distal rectum and anal patency for the colonoscopy and the latter, to perform prostate palpation. In addition, recently graduated doctors report they are insufficiently prepared to perform a complete digital rectal evaluation (18) . Such discrepancy of DRE depending on each examiner, to determine sphincter tonus, motivated this study.…”
Section: Is the Physician Expertise In Digital Rectal Examination Of mentioning
confidence: 99%
“…Moreover, the finding shows that with corresponding training [35], it is possible for PIs to become very well qualified in a very short time.…”
Section: Discussionmentioning
confidence: 99%
“…This equally good result of faculty staff physicians and PIs is particularly striking as the PIs were unable to make any notes during the examination, and had to remember the individual points, while the physicians–as is customary in normal teaching–already made notes for later feedback during the examination. Moreover, the finding shows that with corresponding training [ 35 ], it is possible for PIs to become very well qualified in a very short time.…”
Section: Discussionmentioning
confidence: 99%